Experiences and schooling trajectories of students with disabilities in a secondary school (Itinerarios Educativos, 2024)
In this writing I propose to share some of the experiences of students with disabilities in secondary school. At the same time, I want to share how these experiences were bridges to mobilize teaching practices, the assumptions constructed about trajectories and disability. The expansion of secondary education is an opening event, in which «those unexpected students» enter to challenge the selective bases of a school that insists on maintaining its traditional forms.  The concepts that organize the writing are experiences, paths and disability, these will be analyzed to understand social and school problems around differences from the situation. To do this, I return to part of my own practice as a special education teacher by accompanying the experiences of students and teachers in their encounter with disability. The idea of cronopios that Julio Cortázar creates, gives meaning to what I experienced during my work in a secondary school in the city of Paraná from 2012 to the present
Keywords: experiences; trajectories; disability; secondary school